Terahertz Wave Absorption Property of all Mixed Organic–Inorganic Hybrid Perovskite Thin Film MA(Sn, Pb)(Br, I)3 Fabricated by Sequential Vacuum Evaporation Method - Maeng, Inhee; Tanaka, Hiroshi; Mag-usara, Valynn Katrine; Nakajima, Makoto; Nakamura, Masakazu; Jung, Min-Cherl (Frontiers in Chemistry, 2021)
All mixed hybrid perovskite (MA(Sn,Pb)(Br,I)3) thin film was fabricated by sequential vacuum evaporation method. To optimize the first layer with PbBr2 and SnI2, we performed different annealing treatments. Further, MA(Sn, Pb)(Br, I)3 thin film was synthesized on the optimized first layer by evaporating MAI and post-annealing. The formed hybrid perovskite thin film exhibited absorptions at 1.0 and 1.7 THz with small absorbance (< 10 %). Moreover, no chemical and structural defect-incorporated absorption was found. In this study, the possibility of changing THz absorption frequency through the mixture of metal cations (Sn+ and Pb+) and halogen anions (Br- and I-) was verified.